History Information about Breastfeeding and Its Association with Exclusive Breastfeeding - Khotimah, Kusnul; Isyti’aroh, I (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Exclusive breastfeeding has many benefits for babies, mothers, families, and countries. However, many failure exclusive breastfeeding still happens. The purpose of the study was to determine the relationship between history of exposed information about exclusive breastfeeding and exclusive breastfeeding. The research method used descriptive correlative, and cross sectional data collection. The sampling technique used total sampling. The number of samples was 156. The data were analyzed using Chi square. The results of the analysis of the characteristics respondents, showed that the average age of the mother was 31.37 years, 72% had low education and 82.1% not employed. Analysis of the history of exposed information about exclusive breastfeeding and exclusive breastfeeding showed that of the 135 who were exposed to information about exclusive breastfeeding, 89.89% did not exclusively breastfeed. The p-value is 0.105, which means that there is no relationship between a history of exposed information about exclusive breastfeeding and exclusive breastfeeding. Suggestions for health workers to continue to provide education and assistance when mothers give exclusive breastfeeding so that mothers are successful in exclusive breastfeeding.